2019
DOI: 10.1002/lno.11319
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic influence on the oceanic biological carbon pump in the Scotia Sea as revealed by 18S rRNA gene sequencing of suspended and sinking particles

Abstract: Suspended marine particles constitute most of the particulate organic matter pool in the oceans, thereby providing substantial substrates for heterotrophs, especially in the mesopelagic. Conversely, sinking particles are major contributors to carbon fluxes defining the strength of the biological carbon pump (BCP). This study is the first to investigate the differential influence of eukaryotic communities to suspended and sinking particles, using 18S rRNA gene sequencing on particles collected with a marine sno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 192 publications
(287 reference statements)
8
41
0
Order By: Relevance
“…In our data set, Chytrids were detected, particularly from samples from the AP, but had a low frequency despite often having a high relative abundance in samples where they were present. In Arctic systems Chytrids have been reported as the most abundant fungi group in ice cores (Hassett, Ducluzeau, & Collins, 2017; Hassett & Gradinger, 2016) and seawater (Comeau, Vincent, Bernier, & Lovejoy, 2016), A diversity of Chytrids and other basal fungi have been found in lakes on the Antarctic continent (Rojas‐Jimenez et al., 2017), and in Antarctica soils (Cox, Newsham, & Robinson, 2019) as well as on organic particles in the Scotia sea (Duret et al., 2020). Our study demonstrated the benefit of using a combination of marker genes for epiplastic fungi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our data set, Chytrids were detected, particularly from samples from the AP, but had a low frequency despite often having a high relative abundance in samples where they were present. In Arctic systems Chytrids have been reported as the most abundant fungi group in ice cores (Hassett, Ducluzeau, & Collins, 2017; Hassett & Gradinger, 2016) and seawater (Comeau, Vincent, Bernier, & Lovejoy, 2016), A diversity of Chytrids and other basal fungi have been found in lakes on the Antarctic continent (Rojas‐Jimenez et al., 2017), and in Antarctica soils (Cox, Newsham, & Robinson, 2019) as well as on organic particles in the Scotia sea (Duret et al., 2020). Our study demonstrated the benefit of using a combination of marker genes for epiplastic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, marine plastics are often covered in polysaccharide‐rich diatom biofilms (Lacerda et al., 2019), this could explain the attachment and association of fungi with biofilms on plastics (Kettner, Rojas‐Jimenez, Oberbeckmann, Labrenz, & Grossart, 2017; Oberbeckmann, Osborn, & Duhaime, 2016). Recent studies have directly linked fungi to the degradation of organic matter (Cunliffe, Hollingsworth, Bain, Sharma, & Taylor, 2017;Ortega‐Arbulú, Pichler, Vuillemin, & Orsi, 2019), and in the open ocean fungi may attach to marine snow particles (Bochdansky, Clouse, & Herndl, 2017; Duret, Lampitt, & Lam, 2020). Other marine debris such as wood also harbour fungi, suggesting that Fungi are well adapted to live on different types of floating marine substrates (Kettner, Oberbeckmann, Labrenz, & Grossart, 2019; Kettner et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found an opposite distribution between Acantharea and RAD-B, which showed preference for the upper (<500 m) and deeper (>500 m) mesopelagic samples, respectively (Figure 7). Among Acantharea, most sequences were assigned to the order Chaunchantida (Figure S9, Figure S14), which has been found in sinking particles collected in the Southern Ocean (Duret et al 2020) and the California Current (Gutierrez-Rodriguez et al 2019; Preston et al 2020). In a recent study conducted in the Southern Ocean, RAD B was reported to be enriched in small (<10 µ m) suspended particles relative to sinking particles (Duret et al 2020) while RAD-A were consistently found in sinking particles reaching abyssal depths in the California Current Ecosystem (Preston et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Diatoms of the genus Chaetoceros generally from chain-like structures which in the presence of high levels of biomass, tend to cluster together into larger colonies forming aggregates and producing abundant exopolymeric gels that lead to high carbon export (Chamnansinp et al, 2013;Booth et al, 2002;Duret et al, 2020). This is particularly true in the Baffin Bay, where it has been estimated that in July, cells of C. gelidus can contribute up to 91 and 49% of total phytoplankton abundance and carbon respectively (Booth et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Crustaceans and soft-bodied Urochordata are also known to actively or passively participate in the formation of marine aggregates (Duret et al, 2020). By feeding indiscriminately on organic particles present in the aggregates, N. pachyderma diet could also contain these organisms, or their remains.…”
Section: Discussionmentioning
confidence: 99%